Ecological Fitness of Vibrio cholerae, Vibrio parahaemolyticus, and Vibrio vulnificus in a Small-Scale Population Dynamics Study - Thorstenson, Candice A.; Ullrich, Matthias S. (Frontiers in Marine Science, 2021)
The potential spread of infectious diseases in response to climate change and rising sea surface temperatures in temperate regions has been a growing concern for the past several decades. Extreme heat waves in the North Atlantic and North Sea regions have been correlated with an increase in human Vibrio infections; of particular concern to human health are Vibrio cholerae, V. parahaemolyticus, and V. vulnificus. While these species are well-known to cause disease in humans, most environmental strains are not pathogenic. Studying not only the behavior of the pathogenic strains, but that of non-pathogenic environmental isolates, may better elucidate their ecological relationship in their native microbiome and the dispersal of these species in coastal regions. Using red fluorescent protein-tagged and gentamycin-resistant V. cholerae, V. parahaemolyticus, and V. vulnificus strains, we investigated whether increasing temperatures confer greater competitive fitness to these species when incubated within a natural North Sea water sample still containing its microbiome in a small-scale niche investigation. Increased incubation temperatures alone did not confer a competitive advantage to V. cholerae, V. parahaemolyticus, and V. vulnificus. The microbial community could limit Vibrio growth at all temperatures. To the best of our knowledge, we also demonstrate the first (albeit unintentional) genetic modification of multiple species of marine bacteria through the introduction of a genetically modified V. vulnificus strain into a natural water sample in a contained system.